The role of self-representation in emotional contagion - Wang, Dan; Liu, Changhong; Chen, Wenfeng (Frontiers in Human Neuroscience, 2024)
Although prior research has implied that emotional contagion occurs automatically and unconsciously, convincing evidence suggests that it is significantly influenced by individuals' perceptions of their relationships with others or with collectives within specific social contexts. This implies a role for self-representation in the process. The present study aims to offer a novel explanation of the interplay between social contexts and emotional contagion, focusing on the contextualized nature of self-representation and exploring the social factors that shape emotional contagion. It further posits a causal loop among social contexts, self-representation, and emotional contagion.Drawing from the lens of self-representation, this study concludes with a discussion on potential research directions in this field, commencing with an exploration of the antecedents and consequences of emotional contagion and self-representation.